Determinan Manajemen Laba Dengan Moderasi Komite Audit (Studi Kasus Pada Perusahaan Manufaktur Yang Terdaftar Di Bei Tahun 2018-2020) - Jennifer Chua; Wendy Tania Ruandi; Fery Fery; Anwar R Pangaribuan; Jenny Zain (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The purpose of this study is to see the effect of leverage, size and audit quality on earnings management by moderating the audit committee in manufacturing companies listed on the Stock Exchange, both partially and simultaneously. Profit administration is the impact of using pools in financial planning. The use of the collection premise in the setting of budget articulation does not indicate the possibility that this miracle of profit administration can occur in publicly traded companies around the world, both in the capital markets of developing countries and in the capital markets of countries. develop. The population of this study is a manufacturing company on the IDX for the 2018-2020 period, which is 177 companies and the sample uses a total of 204 units of analysis. The research method applies multiple linear regression analysis techniques. The results of the study mean that leverage and audit quality partially affect earnings management. Size partially has no effect on profit management. The audit committee can strengthen the correlation between leverage and profit management. The audit committee can strengthen the correlation between size and profit management. The audit committee could not strengthen the correlation between audit quality and earnings management. Keywords : Leverage, Size, Audit Quality, Earnings Management, Audit Committee